Legal science and practice: changes of the time - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
This article is about the results of the International conference, where the current issues of the law science development were discussed and the problems of reforming of different areas of a lawyers’ practical activity were being solved. The authors outlined the importance of a discussion of these problems on the international level for the fast reaction of the scientists to the changes of time and for the opportunity to join those legal reforms that take place in Ukraine at the moment. It is also emphasized in the article that the conference was very productive. As a result of reports of 352 participants of the conference from 23 regions of Ukraine and 19 foreign countries, 68 educational institutions and 42 organizations, public associations, a conclusion was made that a practice only can give an answer on the question regarding the correctness of the objective reality’s image in the subjective knowledge. It was also mentioned that a modern legislature doesn’t fall in with the conclusions of the science and legal technique in lots of issues. On the conference the issues of administrative, court system reforms were discussed. Private-legal relations’ subject is an actual issue in both Ukraine and abroad. The scientists who took part in the conference proposed to fix in a Chapter 53 of the Civil Code of Ukraine a general legal obligation of the fair behavior while negotiating and concluding a contract and a civil responsibility for its breach. The participants of the conference also recommended that a Law of Ukraine “On commercial concession” should be enacted. As for the labor law the participants of the conference suggested adding to the new Labor Code of Ukraine the definitions of personal data of a worker according to the international and foreign experience. The authors concluded that reforms that take place in Ukraine nowadays can’t be fully implemented if the scientists are not taking an active part in this process. It was also mentioned that the development of international cooperation is an effective factor of a successful realization of a future strategic scientific projects, and further it will provide an improvement of national legislation, speed up the process of its harmonization with international law.